Phylogenetic relatedness of woody angiosperm assemblages and its environmental determinants along a subtropical elevational gradient in China - Yue, Juan (Plant Divers, 2020)
The species composition of plant communities is determined by a number of factors, including current environmental conditions as well as biogeographical and evolutionary history. Despite evidence that plant diversity decreases and species relatedness increases along latitudinal and environmental gradients (e.g., low temperatures), it remains unclear whether these same patterns occur along elevational gradients, especially in the subtropical mountainous areas harboring rich biodiversity. In this study, we explored the pattern of phylogenetic relatedness of woody angiosperm assemblages and examined the effects of temperature variables on the phylogenetic relatedness among angiosperm woody plants using generalized linear model in subtropical forest communities along a broad elevational gradient in the Dulong Valley of Yunnan Province, China. Our results showed that woody angiosperm species in local forest plots tend to be more phylogenetically related at higher elevations and in areas with lower temperatures. Additionally, winter average temperature, rather than mean annual temperature, is a major predictor of the pattern of increasing phylogenetic relatedness with increasing elevation. This finding is consistent with the prediction of ‘Tropical Niche Conservatism’ hypothesis, which highlights the role of niche constraints in driving phylogenetic community assembly along an elevational gradient.